Condition Survey Of Badminton Enthusiasts In Sragen Regency In 2023 - Sunjoyo; Sholeh, Muchhamad; Sakti Rumpoko, Satrio; Septi Sistiasih, Vera; Kuntum Mandalawati, Titin; Rasyid, Anwar (Universitas Tunas Pembangunan Surakarta, 2024)
Physical fitness is one of the important physical components and must be owned by athletes to support in the game of badminton. This study aims to determine Physical Conditions which include Arm Muscle Strength, Flexibility, Leg Muscle Power, and Speed of Sragen Regency Badminton Athletes in 2023. The research method used is the Survey method. The study population numbered 60 people. Sampling using purposive sampling technique. Data collection techniques using Tests and Measurements. Data analysis techniques use descriptive statistical techniques. The results of the study were obtained that: Physical Condition Survey of Badminton Athletes in Sragen Regency in 2023 in the